Nutrition knowledge level of nurses - (:unkn) unknown (My University, 2013)
Background: Concern is growing about the malnutrition, nutrition therapy and its complications. Reduced involvement of nurses in patients' nutritional care may be one of the contributing factors. The most common cause for insufficient nutritional practice is lack of nutritional knowledge. The purpose of the study was to determine knowledge-based nutrition competencies of nurses. Method and Material: A sample of 302 nurses from different hospitals in Zonguldak in Turkey and who were selected randomly completed a questionnaire. Results: The mean clinical nutrition knowledge of all participants was obtained as 49.44±10.95 over 100 points. Nurses who conducted nutritional assessment activities had a statistically significant higher knowledge scores compared to the those who did not (p=0.012). Conclusions: The nurse education institutions should review their curriculum regarding the education about clinical nutrition and a systematic continuing nutrition education program should be arranged.
Keywords: Clinical nutrition; Knowledge; Nurses